Difference Cordial Labeling of Arrow Graph - J. Arthy; K. Ramanathan; K. Manimekalai (International Journal of Mathematics And its Applications, 2018)
In this work we establish the difference cordial labeling of arrow graphs $A_n^2$, $DA_n^2$, $A_n^m$ and $DA_n^m$.